Electrolyte and preparation method and application thereof

By using cation trapping agents and large metal ions in the electrolyte, the problems of structural distortion and side reactions of Prussian blue materials during charging and discharge are solved, and the structural stability of the material and the cycling performance of the battery are significantly improved.

CN119481293AInactive Publication Date: 2025-02-18NINGBO RONBAY LITHIUM BATTERY MATERIAL CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202510026135.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-08
Publication Date
2025-02-18
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

During the charging and discharging process of Prussian blue materials, metal ion dissolution, structural distortion and electrolyte side reactions are prone to metal ion dissolution, resulting in poor circulation performance.

Method used

Using an electrolyte containing a cation trap and a metal ion having an ion radius greater than or equal to 80 nm, a cation trap such as ferrocyanate can capture the dissolved transition metal ions, while a large metal ions can inhibit the reabsorption of Prussian blue materials. .

Benefits of technology

It effectively reduces the transition metal ion content in the electrolyte, inhibits the structural distortion of Prussian blue material and the side reaction of electrolyte, and improves the structural stability of the material and the cycling performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119481293A_ABST
    Figure CN119481293A_ABST
Patent Text Reader

Abstract

The invention provides an electrolyte and a preparation method and application thereof, the electrolyte is used for a battery containing Prussian blue and analogues thereof, the electrolyte comprises a cation trapping agent and one or more of metal ions with the ion radius larger than or equal to 80 nm, and the cation trapping agent comprises a chelating agent. The present invention contributes to the improvement of the cycle performance of batteries containing Prussian blue and analogues thereof.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of electrolytes, and in particular to an electrolyte and a preparation method and application thereof. Background Art

[0002] Prussian blue materials can be used as positive electrode materials for sodium batteries. For example, Prussian white has a three-dimensional skeleton structure that is conducive to ion migration, a high specific capacity (170 mAh / g, simple and inexpensive raw materials and synthesis process), and is one of the more ideal positive electrode materials for sodium batteries. In particular, manganese-based Prussian white has a high specific capacity and platform voltage, can provide higher energy density, and is widely available and inexpensive, making it an ideal high-energy density material.

[0003] However, Prussian blue materials also have the problem of transition metal dissolution. For example, manganese (Mn) ions in manganese-based Prussian blue materials have more variable valence states and higher platform voltages, which are more prone to metal ion dissolution / strong redox side reaction valence changes in the high-voltage region of the charge and discharge process, leading to structural distortion and the Jan-Taylor effect. These will cause the manganese (Mn) ions in manganese-based Prussian blue materials to continue to lose during the cycle, and the Mn-CN-M (Mn or other metal ions) bonds to be severely deformed or even broken, causing structural distortion and collapse, increasing electrolyte side reactions, and severely limiting the long-cycle performance of this type of material. At the same time, in addition to inert Ni ions, other transition metals (such as Fe, Cu, Co, etc.) are also prone to dissolution, leading to structural collapse.

[0004] In addition, although the crystalline water content in Prussian blue materials (Prussian white materials) can be reduced by drying, the crystalline water in Prussian blue materials (Prussian white materials) may still escape under high temperature and high pressure during the charge and discharge process, and will react with Na + Combine to form Na(OH2) + The compound enters the Prussian blue material (Prussian white material) lattice again to occupy the active site, destroying the original structure of rhombus and cubic, causing cycle attenuation and affecting the electrochemical performance. + Repeated embedding and de-embedding can easily cause the structure of Prussian materials (Prussian blue-type materials) to deform, leading to volume changes or surface cracks, destroying the crystal structure and being detrimental to cycle performance.

[0005] Therefore, how to improve the structural stability of Prussian blue materials is a research hotspot in this field. Summary of the invention

[0006] The invention provides an electrolyte and a preparation method and application thereof, which are helpful to improve the structural stability of Prussian blue and its analogs and improve the cycle performance of the battery.

[0007] The present invention provides an electrolyte, which is used for a battery containing Prussian blue and its analogs. The electrolyte comprises a cation capture agent and one or more metal ions with an ion radius greater than or equal to 80nm, wherein the cation capture agent comprises a chelating agent.

[0008] Optionally, the cation capture agent includes one or more of ferrocyanate, amines, ascorbic acid, and oxalate; the ferrocyanate includes one or more of sodium ferrocyanate and potassium ferrocyanate, and the oxalate includes sodium oxalate; the amines include one or more of coconut amine, dodecylamine, and octadecylamine; and / or, in the electrolyte, the concentration of the cation capture agent is 1~50mmol / L.

[0009] Optionally, in the electrolyte, the concentration of the metal ions with an ion radius greater than or equal to 80 nm is 0.01-0.5 mol / L; and / or, the metal ions with an ion radius greater than or equal to 80 nm include one or more of calcium, barium, cesium, and silver.

[0010] Optionally, the chemical formula of the Prussian blue and its analogs is Na x Mn y Fe z Ni α [Fe(CN)6] β nH2O, where 1.0≤x≤1.5, 0.4≤y≤0.6, 0.4≤z≤0.6, 0.01≤α≤0.03, y+z+α=1, 0.6≤β≤0.8, 0.5≤n≤3.

[0011] Optionally, the electrolyte further includes electrolyte salt, organic solvent, and film-forming additives, wherein the electrolyte salt includes one or more of sodium perchlorate, sodium hexafluorophosphate, sodium tetrafluoroborate, and organic sodium salt; the organic solvent includes one or more of ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, and vinyl sulfate; the film-forming additive includes one or more of fluoroethylene carbonate, ethylene carbonate, vinyl carbonate, and polystyrene.

[0012] Optionally, in the electrolyte, the concentration of the electrolyte salt is 0.3~1.5 mol / L; and / or the ratio of the volume of the organic solvent to the volume of the electrolyte is 75%~95%; and / or the ratio of the volume of the film-forming additive to the volume of the electrolyte is 0~5%.

[0013] Optionally, the water content of the electrolyte is less than 50 ppm, the hydrohalic acid content is less than 30 ppm; and / or, at 20-25° C., the conductivity of the electrolyte is 10 -3 ~10 -8mS / cm, viscosity of 5 to 50 mPa·s; and / or, the salting-out temperature of the electrolyte is -25 to 0°C, the application window of the electrolyte is 1.5 to 4.5V, and in a battery containing Prussian blue and its analogs, the characteristic peak of the film-forming potential of the electrolyte is 2.1 to 3.2V.

[0014] The present invention also provides a method for preparing the electrolyte as described above, comprising: dissolving the cation capture agent and or a metal salt including the metal ion with an ion radius greater than or equal to 80 nm in a raw material system including an organic solvent to obtain the electrolyte.

[0015] Optionally, it also includes: mixing a film-forming additive and an organic solvent to obtain the raw material system including the organic solvent; dissolving an electrolyte salt in the raw material system including the organic solvent, and then dissolving the cation capture agent and a metal salt including the metal ion with an ion radius greater than or equal to 80 nm therein to obtain the electrolyte.

[0016] The present invention also provides a battery, comprising a positive electrode sheet containing Prussian blue and the like and the electrolyte as described above.

[0017] The invention provides an electrolyte, a preparation method and application thereof. A cation capture agent can capture transition metals dissolved from Prussian blue and its analogues in the electrolyte, thereby reducing the transition metal content in the electrolyte. Metal ions with an ion radius greater than or equal to 80 nm help to inhibit repeated water absorption by Prussian blue and its analogues, thereby protecting Prussian blue and its analogues, improving the structural stability of Prussian blue and its analogues, reducing side reactions of the electrolyte, and helping to maintain the integrity of a diaphragm, thereby helping to improve the cycle performance of a battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0019] Figure 1 The battery cycle performance diagram of Examples 1-3 and Comparative Example 1;

[0020] Figure 2 This is a cross-sectional scan of the broken positive electrode material of Comparative Example 1 after 200 cycles;

[0021] Figure 3 This is a scan of the broken positive electrode material of Example 1 (sodium ferrocyanide additive is added to the electrolyte alone) after 200 cycles;

[0022] Figure 4 This is a scan of the broken positive electrode material of Example 2 (barium perchlorate additive is added to the electrolyte alone) after 200 cycles;

[0023] Figure 5 This is a scan of the broken positive electrode material of Example 3 (sodium ferrocyanide and barium perchlorate additives were added to the electrolyte) after 200 cycles;

[0024] Figure 6 The figure shows the disassembled batteries of Examples 1-3 and Comparative Example 1 ( Figure 6 a1 is a disassembled picture of the battery of comparative example 1 without any additives, b1 is a disassembled picture of the battery of example 1 with calcium perchlorate added, c1 is a disassembled picture of the laminated battery of example 2 with sodium ferrocyanide modified electrolyte added, d1 is a disassembled picture of the battery of example 3 with both sodium ferrocyanide and calcium perchlorate electrolyte added). DETAILED DESCRIPTION

[0025] In order to make the purpose, technical solutions and advantages of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0026] Most existing technologies improve the structural stability of Prussian blue materials by increasing crystallinity or doping / coating with inert metals (Cu / Ni), but the overall effect is not obvious, and the degree of coating or doping uniformity is difficult to control, and it is difficult to avoid the degradation of Prussian blue materials during battery cycling. In addition, most electrolytes use organic (containing fluorine, benzene rings or multiple groups) additives to assist in the formation of SEI / CEI layers, but the cost is high, and the additional complex organic substances have a greater impact on ionic conductivity, electrolyte post-treatment and high-voltage multi-side reactions, and fail to improve the structural stability of Prussian blue materials during battery cycling.

[0027] In order to overcome the defects in the prior art, an embodiment of the present invention provides an electrolyte for a battery containing Prussian blue and its analogs, the electrolyte comprising a cation capture agent and one or more metal ions with an ion radius greater than or equal to 80 nm, wherein the cation capture agent comprises a chelating agent.

[0028] According to the inventor's research and analysis: the above-mentioned chelating agent (cation capture agent) can undergo a chelating reaction with transition metal ions, and then can capture transition metal ions including manganese, iron, nickel, cobalt, copper, etc. dissolved by Prussian blue and its analogs, reduce the content of the above-mentioned transition metal ions in the electrolyte, thereby reducing the side reactions of the electrolyte (salting, double decomposition), and also reduce the pollution of these transition metal ions to the diaphragm, which helps to keep the diaphragm intact, avoid obvious problems such as sticking, discoloration and electrolyte salt deposition, and improve the capacity retention rate of the battery. In addition, metal ions with an ion radius greater than or equal to 80nm can exchange metals with Prussian blue and its analogs. While occupying the active sites inside the framework of Prussian blue and its analogs, these metal ions with an ion radius greater than or equal to 80nm have a larger ion size, so they can hinder the reaction of Na + The larger volume of Na(OH2) + The hydrated molecules are immersed in the framework, thus preventing Prussian blue and its analogs from reabsorbing water, while not hindering the small volume of Na + Normal migration, that is, metal ions with an ion radius greater than or equal to 80nm (large metal ions) can inhibit water from re-entering the lattice of Prussian blue and its analogs, and the inhibition rate can be as high as 90% or more, which effectively solves the problem of water reabsorption that cannot be inhibited by common Ni, Co, and Fe doping / coating. Compared with the methods for improving the stability of Prussian blue and its analogs in the prior art (such as Ni doping), these large metal ions (such as Ca 2+ )) enters the interior of the material and does not participate in the redox change itself, which can further improve the stability of the framework structure of Prussian blue and its analogues.

[0029] Therefore, the electrolyte of the embodiment of the present invention is suitable for sodium ion batteries containing Prussian materials, can protect Prussian blue and its analogs, can improve the structural stability of Prussian blue and its analogs, has fewer side reactions, helps to maintain the integrity of the diaphragm, and helps to improve the cycle performance of the battery. For example, after 200 cycles, the capacity retention rate of the battery can still be maintained at 80% or above.

[0030] The cation scavenger in the above electrolyte has the function of inhibiting the metal loss and structural disintegration of the positive electrode material (Prussian blue and its analogues), so that the grain structure of the positive electrode material is effectively protected. In some embodiments, under the protective effect of the above electrolyte, after 200 cycles, the degree of grain breakage of the positive electrode material is less than 35% (SEM area), preferably less than 10%, the porosity of the positive electrode material is less than 20% (compaction, SEM test), preferably less than or equal to 15%, and the width of the crack on the surface of the positive electrode material grain with a particle size of 5μm is less than or equal to 1.5 microns, preferably less than 50nm, and the length is less than or equal to 4.5 microns, preferably less than 2μm.

[0031] In specific implementation, the cycled battery can be disassembled, the positive electrode sheet can be taken out, and the positive electrode material on the positive electrode sheet can be scraped off, and then the degree of grain breakage, porosity, width and length of cracks on the grain surface can be tested respectively, including:

[0032] Use a scanning electron microscope to photograph the grains and cross-sections of the positive electrode material, and observe and calculate the percentage of broken particles in the SEM area (the degree of grain breakage);

[0033] The positive electrode material scraped off is ground using an ion milling device to obtain positive electrode material grains with a particle size of 5 μm, and then photographed using a scanning electron microscope to measure the width and length of cracks on the surface of the positive electrode material grains with a particle size of 5 μm;

[0034] The porosity was measured using scanning electron microscopy (SEM) and Best et al.

[0035] In some embodiments, the cation capture agent includes one or more of ferrocyanate (ferrocyanide compound), amines (amines and their salts), ascorbic acid, and oxalate. These cation capture agents can chelate with transition metal ions including manganese, iron, nickel, cobalt, copper, etc. dissolved by Prussian blue and its analogs, thereby reducing the content of transition metal ions in the electrolyte, thereby reducing the side reactions (salting, double decomposition) of the electrolyte, and also reducing the contamination of the diaphragm by these transition metal ions, which helps to keep the diaphragm intact and avoid problems such as obvious sticking, discoloration, and electrolyte salt deposition.

[0036] The ferrocyanide may include one or more of sodium ferrocyanide and potassium ferrocyanide, the oxalate may include sodium oxalate, and the amine may include one or more of coconut amine, dodecylamine, and octadecylamine.

[0037] Preferably, in an electrolyte (modified electrolyte) including a ferrocyanate additive, the ferrocyanate as a cation capture agent is one of the raw materials for the synthesis of Prussian white, is cheap and readily available, and does not produce additional side reactions / by-products in the battery. It can also capture dissolved transition metal ions (dissolved metal cations) and continuously react on the surface of Prussian blue and its analogs to generate new Prussian blue shells, thereby inhibiting the dissolution of metal cations such as Mn, Fe, and Co during the battery charge and discharge process, preventing further deformation and collapse of the structure, and also helping to reduce the side reactions of the above-mentioned dissolved metal cations with the electrolyte, helping to solve the problem of poisoning treatment in product recovery. It has a certain degree of universality and is generally applicable to Prussian blue / Prussian white positive electrode materials containing soluble metal ions such as Mn, Ni, and Fe, and has good adaptability, and has a good effect of capturing the above-mentioned soluble metal ions and improving the structural stability of the positive electrode material. For example, sodium ferrocyanide Na4Fe(CN)6 can be used as a cation scavenger in the electrolyte and is suitable for Mn / Fe-based Prussian white / blue cathode materials. These cathode materials easily dissolve Mn during the charge and discharge process. 2+ , Fe 2+ , and Na4Fe(CN)6 in the electrolyte will react with the dissolved Mn 2+ / Fe 2+ Continuously reacting on the surface of Prussian blue to generate a new Mn / Fe-based Prussian blue shell can protect and repair Prussian blue and its analogs, thereby preventing further collapse of the Prussian blue structure, improving the structural stability of Prussian blue and its analogs, reducing side reactions, helping to maintain the integrity of the diaphragm, and helping to improve the cycle performance of the battery.

[0038] Na4Fe(CN)6 will react with the dissolved Mn 2+ The reaction equation is as follows:

[0039]

[0040] Na4Fe(CN)6 and free Mn 2+ The shell thickness of the pure Mn-based Prussian blue generated by the reaction is 4~50nm, corresponding to a single peak at 16.8° in the X-ray diffraction (XRD) spectrum.

[0041] Na4Fe(CN)6 and free Fe 2+ The Fe-based Prussian blue shell generated by the reaction corresponds to a single peak at 16.6° in the X-ray diffraction (XRD) spectrum.

[0042] In the above electrolyte, the concentration of the cation capture agent can be 1~50mmol / L, for example, 1, 4, 10, 20, 30, 40, 50mmol / L or a range consisting of any two of them, which can chelate with transition metal ions including manganese, iron, nickel, cobalt, copper, etc. dissolved by Prussian blue and its analogs, thereby reducing the content of transition metal ions in the electrolyte, thereby reducing the side reactions of the electrolyte (salting, double decomposition), and reducing the contamination of the diaphragm by these transition metal ions, which helps to keep the diaphragm intact and avoid obvious problems such as sticking, discoloration and electrolyte salt deposition.

[0043] Battery testing requires that the water content of the electrode be around 1000 ppm, but Prussian blue and its analogs (Prussian blue positive electrode) are easy to absorb water. For example, the Prussian blue positive electrode prepared under low dew point still has a water content of no less than 1000 ppm. Under high voltage of charge and discharge, the water in it can easily escape into the electrolyte, causing decomposition side reactions to produce more water, or return to the Prussian blue structure through repeated absorption, causing structural deformation and collapse, resulting in the disintegration and peeling of the positive electrode material from the electrode.

[0044] The above metal ions with ionic radius greater than or equal to 80nm (large radius metal ions) can exchange metals with Prussian blue and its analogs. While occupying the active sites inside the framework of Prussian blue and its analogs, these metal ions with ionic radius greater than or equal to 80nm have a larger ionic size, so they can hinder the reaction of Na + The larger volume of NaH2O + The hydrated molecules are immersed in the interior of the framework, thereby preventing Prussian blue and its analogues from reabsorbing water, and at the same time will not hinder the normal migration of small-volume Na+. In addition, the above-mentioned metal ions with an ion radius greater than or equal to 80nm do not undergo obvious redox reactions and will not cause structural distortion. Therefore, the problem of water reabsorption is solved from a structural or physical level, and the stability of the framework structure of Prussian blue and its analogues is improved. In addition, the moisture content in the electrode containing Prussian blue and its analogues during the cycle process can also be reduced, the problem of material falling off at the edge of the electrode can be alleviated, and the electrochemical stability of the battery can be improved.

[0045] The metal ions with ion radius greater than or equal to 80 nm in the electrolyte can also help to increase the conductivity of the electrolyte and reduce the viscosity. In some embodiments, at 20-25°C (normal temperature), the conductivity of the electrolyte is 10 -3 ~10 -8 mS / cm, viscosity is 5~50mPa·s.

[0046] The metal ions having an ionic radius greater than or equal to 80 nm may include calcium (Ca 2+ ), barium (Ba 2+ ), cesium (Cs+ ), silver (Ag + ) or more. These inert metal ions with an ionic radius greater than or equal to 80 nm can undergo metal exchange with Prussian blue and its analogs, such as calcium (Ca) in the electrolyte. 2+ ) can partially replace the iron (Fe) in the internal framework of Prussian blue and its analogs 2+ ), while occupying the active sites inside the framework of Prussian blue and its analogs, these metal ions with ionic radius greater than or equal to 80 nm have a larger ionic size, thus hindering the + The larger volume of NaH2O + The hydrated molecules are immersed in the framework, thus preventing Prussian blue and its analogs from reabsorbing water, effectively inhibiting the water that escapes from the lattice in the high-pressure area from re-entering the interior of the Prussian blue material, while not hindering the small volume of Na + Normal migration further improves the framework structure stability of Prussian blue and its analogues.

[0047] In the electrolyte, the concentration of the metal ions having an ion radius greater than or equal to 80 nm may be 0.01-0.5 mol / L, for example, 0.01, 0.1, 0.2, 0.3, 0.4, 0.5 mmol / L or a range consisting of any two thereof.

[0048] It is understandable that the metal ions (cations) with an ion radius greater than or equal to 80 nm in the above electrolyte can be provided by the corresponding inorganic metal salts in the electrolyte, for example, calcium perchlorate can provide Ca 2+ , barium perchlorate can provide Ba 2+ , silver perchlorate can provide silver ions. The anions in these inorganic metal salts can include PF6 - 、ClO4 - , Cl - 、NO3 - At least one of .

[0049] In some embodiments, the electrolyte includes the above-mentioned cation capture agent and metal ions with an ion radius greater than or equal to 80 nm, and the two produce a synergistic effect, which can better improve the stability of the framework structure of Prussian blue and its analogs, improve the cycle stability, and improve the capacity retention rate.

[0050] The cation capture agent (such as sodium ferrocyanide) and the inorganic metal salt providing metal ions with an ion radius greater than or equal to 80 nm in the embodiment of the present invention do not contain crystal water, which helps to reduce the water content of the electrolyte.

[0051] In principle, the electrolyte of the embodiment of the present invention is suitable for all Prussian blue and its analogues, such as Prussian blue / white materials and their analogues. The electrolyte can directly act on the interior of the lattice of Prussian blue and its analogues (Prussian blue / white materials) and the metal ions released by decomposition, and can protect and repair Prussian blue and its analogues, thereby preventing further collapse of the Prussian blue structure, and can improve the structural stability of Prussian blue and its analogues, with fewer side reactions, which helps to maintain the integrity of the diaphragm and helps to improve the cycle performance of the battery.

[0052] In some embodiments, the Prussian blue and its analogs include iron-doped Prussian blue. Specifically, the chemical formula of the Prussian blue and its analogs can be Na x Mn y Fe z Ni α [Fe(CN)6] β nH2O, where 1.0≤x≤1.5, 0.4≤y≤0.6, 0.4≤z≤0.6, 0.01≤α≤0.03, y+z+α=1, 0.6≤β≤0.8, 0.5≤n≤3.

[0053] The electrolyte may include an oil-based sodium electrolyte to avoid the problem that the Prussian blue / white material is more easily dissolved in water, and can enhance the effect of the cation capture agent in capturing cations. Metal ions with an ion radius greater than or equal to 80 nm are more stable in an oil-based environment with low water oxygen value and the same anions, thereby avoiding redox reactions in the water system.

[0054] It is understandable that the above electrolyte may also include electrolyte salt, organic solvent, and film-forming additive.

[0055] The electrolyte salt may include a metal sodium salt, for example, one or more of sodium perchlorate (NaClO4), sodium hexafluorophosphate (NaPF6), sodium tetrafluoroborate (NaBF4), and an organic sodium salt (NaTDI). In the electrolyte, the concentration of the electrolyte salt may be 0.3-1.5 mol / L.

[0056] The organic solvent may include an organic ester solvent, for example, one or more of ethylene carbonate (EC), propylene carbonate (PC), dimethyl carbonate (DMC), diethyl carbonate (DEC), and vinyl sulfate (DTD), and the ratio of the volume of the organic solvent to the volume of the above-mentioned electrolyte may be 75% to 95%;

[0057] The film-forming additive may include one or more of fluoroethylene carbonate (FEC), ethylene carbonate, vinyl carbonate (VEC), and polystyrene (PS), and the ratio of the volume of the film-forming additive to the volume of the electrolyte may be 0-5%.

[0058] In some embodiments, the water content of the electrolyte of the embodiments of the present invention is less than 50 ppm, and the content of halogen acid (such as hydrogen fluoride HF and hydrogen chloride HCl) is less than 30 ppm.

[0059] In some embodiments, the salting-out temperature of the electrolyte is -25 to 0°C, and the application window of the electrolyte is 1.5 to 4.5V.

[0060] In a battery containing Prussian blue and its analogs, when the organic solvent of the electrolyte includes ethylene carbonate (EC) and / or propylene carbonate (PC), the characteristic peak of the film-forming potential of the electrolyte is 2.1-3.2V.

[0061] The water content of the electrolyte can be tested by the Karl Fischer water test method, the content of halogen acid (such as hydrogen fluoride HF and hydrogen chloride HCl) can be tested by gas chromatography, the salting-out temperature is obtained by testing at different temperatures (such as controlled by a freezer), the application window of the electrolyte can be tested by linear sweep voltammetry (LSV), and in batteries containing Prussian white / blue compounds, when the organic solvent of the electrolyte includes ethylene carbonate (EC) and / or propylene carbonate (PC), the detection method of the characteristic peak of the film-forming potential of the electrolyte can be carried out by the CV (cyclic voltammetry test) of the electrochemical workstation.

[0062] The embodiments of the present invention also provide a method for preparing the above-mentioned electrolyte, comprising: dissolving the above-mentioned cation capture agent and or a metal salt including the above-mentioned metal ion with an ion radius greater than or equal to 80 nm in a raw material system including an organic solvent to obtain the above-mentioned electrolyte.

[0063] The preparation method has simple process, the raw materials used are all common materials, the price is low and the post-processing is simple.

[0064] It can be understood that the metal cations corresponding to the metal salts including the metal ions having an ionic radius greater than or equal to 80 nm include the metal ions having an ionic radius greater than or equal to 80 nm.

[0065] The preparation method further includes: mixing a film-forming additive and an organic solvent to obtain a raw material system including an organic solvent; dissolving an electrolyte salt in the raw material system including an organic solvent, and then dissolving the cation capture agent and a metal salt including a metal ion with an ion radius greater than or equal to 80 nm therein to obtain an electrolyte. For example, in a vacuum glove box, a film-forming additive and an organic solvent (for example, EC, DMC, DEC in a ratio of 40:35:20) are mixed at room temperature and stirred for 2 to 12 hours to obtain a raw material system including an organic solvent (electrolyte base solvent), and then an electrolyte salt is added to the raw material system including an organic solvent and stirred for 12 to 24 hours until it is completely dissolved, and then a cation capture agent (for example, sodium ferrocyanide) and a metal salt including a metal ion with an ion radius greater than or equal to 80 nm (for example, Ca(ClO4)2) are added thereto at 10 to 120°C, for example, 10, 60, 100, 120°C or a range consisting of any two thereof, and stirred for 1 to 48 hours, for example, 1, 60, 100, 120°C or a range consisting of any two thereof, until it is completely dissolved to obtain a transparent electrolyte solution.

[0066] In the above preparation method, in order to promote the dissolution of the metal salt, a small amount of ethylene glycol may be added to assist the dissolution until the metal salt is completely dissolved.

[0067] In the above preparation method, the temperature for mixing the raw materials can be 10-120° C. and the mixing time can be 1-48 hours.

[0068] In addition, the preparation of the electrolyte according to the embodiment of the present invention can be carried out under the protection of an inert gas, such as at least one of nitrogen N2, argon Ar, helium He, and neon Ne.

[0069] The embodiment of the present invention further provides a battery, comprising a positive electrode sheet containing Prussian blue and its analogues and the above-mentioned electrolyte. The positive electrode sheet comprises a positive electrode current collector and a positive electrode active material layer located on at least one side surface of the positive electrode current collector, and the positive electrode active material layer comprises the above-mentioned Prussian blue and its analogues. The embodiment of the present invention can compensate for the structural instability or collapse caused by the dissolution of metal ions such as manganese, iron, nickel and the reabsorption of water during the battery cycle of the above-mentioned Prussian blue and its analogues, and helps to improve the cycle performance of the battery.

[0070] The Prussian blue and the like mentioned above include at least one of Prussian white, Prussian blue and the like.

[0071] The present invention does not limit the preparation process of the above-mentioned Prussian blue and its analogs, and they can be prepared according to the conventional process in the art. For example, manganese-iron Prussian blue and its analogs (Mn-Fe Prussian blue and its analogs) can be prepared by the following process: a mixed solution of manganese sulfate solution and sodium ferrocyanide solution (the concentration ratio of the two can be 2:1) is pumped into a base solution containing sodium sulfate and sodium ferrocyanide (while stirring at a constant temperature of 25°C) to obtain manganese-iron Prussian white, and then the temperature is raised to 60-80°C, for example, 60°C, 7 0℃, 80℃ or any two of them, and aged at a lower speed (100~300rpm) for 6~8h; then after the temperature is lowered to 25℃, manganese sulfate, ferric sulfate mixed solution (the concentration ratio of the two can be 2:1) and sodium ferrocyanide solution are pumped into the above solution again. After the reaction is completed, the temperature is kept constant at 25℃ and aged at a lower speed (100~300rpm) for 2~8h to obtain manganese iron Prussian blue positive electrode material (nitrogen protection is always maintained during the synthesis).

[0072] The embodiment of the present invention does not limit the concentration and addition amount of various raw materials required for the preparation of the above-mentioned Prussian blue and its analogs, and can be set according to actual needs.

[0073] The embodiment of the present invention does not limit the preparation process of the positive electrode sheet, and it can be prepared according to the conventional process in the art. For example, the above-mentioned Prussian blue and its analogs can be dried at 110~130°C, for example, 110, 120, 130°C or a range composed of any two thereof, and then ball-milled and mixed evenly with the conductive agent and the binder, and then evenly coated on the positive electrode current collector. The coating thickness can be 50~300 mm (for example, 50~200 mm), and the positive electrode sheet is obtained by roller pressing at 150~200°C. After drying at above 100°C for 24 hours, it can be assembled into a battery with materials such as the negative electrode sheet.

[0074] Among them, the material of the positive electrode current collector can be at least one of aluminum foil and nickel foil; the conductive agent can be selected from at least one of conductive carbon black (SP), carbon black, acetylene black, graphene, Ketjen black, and carbon fiber; the binder can be selected from at least one of polytetrafluoroethylene (PTFE), polyvinylidene fluoride, polyvinyl fluoride, polyethylene, polypropylene, polyvinyl alcohol, carboxymethyl cellulose, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, ethylene oxide-containing polymers, polyvinyl pyrrolidone, and polyurethane.

[0075] It is understandable that the above-mentioned battery also includes a negative electrode sheet and a separator arranged between the negative electrode and the positive electrode.

[0076] The embodiments of the present invention do not strictly limit the negative electrode active material in the negative electrode sheet, and may be a negative electrode active material commonly used in current sodium ion batteries, such as at least one of hard carbon, soft carbon, titanium-based materials, metal oxides and sulfides.

[0077] The embodiment of the present invention does not strictly limit the material selection of the diaphragm, and it can be a diaphragm material commonly used in sodium ion batteries, such as a polypropylene diaphragm (PP), a polyethylene diaphragm (PE), a polypropylene / polyethylene double-layer composite film (PP / PE), a polyimide electrospinning diaphragm (PI), a polypropylene / polyethylene / polypropylene three-layer composite film (PP / PE / PP), a cellulose non-woven fabric diaphragm, and a diaphragm with a ceramic coating.

[0078] When preparing sodium-ion batteries, the positive electrode sheet, separator and negative electrode sheet are wound or stacked to obtain a bare cell, and the bare cell is packaged in a pre-stamped aluminum-plastic film bag. After the packaged battery is dried at 85°C, the electrolyte is injected into the dry battery. After the battery is shelved, formed and sealed for the second time, the preparation of the sodium-ion battery is completed.

[0079] In some embodiments, under the protection of the above-mentioned electrolyte, after 1000 cycles of charge and discharge, the moisture content of the positive electrode sheet (Prussian blue electrode sheet) containing Prussian blue and its analogues is ≤800ppm, for example, about 500ppm, which proves that it is difficult for moisture to escape from the material in the high voltage section of the cycle process and return to the interior of the positive electrode. In addition, the metal ion loss problem of Prussian blue and its analogues is suppressed, and the concentration of metal ions dissolved from Prussian blue and its analogues (Prussian blue material) in the electrolyte is below 500 ppm. At the same time, since the loss of moisture and metal is suppressed, the disintegration and detachment of the positive electrode material is reduced, and the positive electrode peeling force is ≥1.5N. The specific test process may include: discharging in a dry room and disassembling the laminated soft-pack battery after the cycle (for example, 200 to 1000 cycles), taking out the corresponding positive and negative electrodes and vacuum-sealing them for sample testing of card moisture, and at the same time, performing X-ray diffraction (XRD) on the electrode to test the loss of metal ions such as Fe, Mn, and Ni in it, using inductively coupled plasma (metal ICP) to test the metal ion concentration of such Prussian blue materials in the electrolyte, fixing the positive electrode on a peeling force tester, for example, using tape to fix the positive electrode on the peeling force tester, and performing mechanical testing to obtain the positive electrode peeling force (electrode peeling force).

[0080] In addition, direct observation and scanning electron microscopy observation revealed that the above electrolyte helps to reduce the contamination of the diaphragm by these transition metal ions, helps to maintain the integrity of the diaphragm, and avoids obvious problems such as sticking, discoloration, and electrolyte salt deposition.

[0081] In some embodiments, the Ca in the Prussian blue electrode 2+ and / or Ba 2+The ion concentration is between 400 and 1000 ppm. After the corresponding cycle (e.g., 50 cycles), the electrode has new characteristic peaks at 21.3° and 31.0° in XRD (the formed Na x- 2y Ca y Mn(CN)6 compounds).

[0082] The present invention is described in more detail below through specific embodiments.

[0083] Example 1

[0084] This embodiment provides a method for preparing an electrolyte, comprising:

[0085] 1) Mixing fluoroethylene carbonate (FEC), ethylene carbonate (EC) and dimethyl carbonate (DMC) to obtain an electrolyte base solvent; wherein the volume ratio of ethylene carbonate (EC) to dimethyl carbonate (DMC) is 1:1, and the total volume of ethylene carbonate (EC) and dimethyl carbonate (DMC) is 100 mL, and the volume percentage of fluoroethylene carbonate (FEC) in the above electrolyte base solvent is 5%;

[0086] 2) Then, 12.44 g NaClO4 (i.e., the concentration of NaClO4 in the electrolyte is 1 mol / L) is added to the electrolyte base solvent and stirred until completely dissolved;

[0087] 3) Then, at 60°C, 3.362 g (i.e., the concentration of Ca(ClO4)2 in the electrolyte is 0.1 mol / L) of Ca(ClO4)2 was added and stirred for 24 h to obtain a transparent solution, which is the electrolyte of Example 1 (named B24-0618-B).

[0088] Example 2

[0089] This embodiment is basically the same as Embodiment 1, except that:

[0090] Step 3) includes: then adding 0.0303 g (ie, the concentration of sodium ferrocyanide in the electrolyte is 1 mmol / L) of sodium ferrocyanide at 60° C. and stirring for 24 hours to obtain a transparent solution, which is the electrolyte of Example 2 (named B24-0618-Y).

[0091] Example 3

[0092] This embodiment is basically the same as Embodiment 1, except that:

[0093] Step 3) includes: then at 60°C, adding 0.0303 g (i.e., the concentration of sodium ferrocyanide in the electrolyte is 1 mmol / L) of sodium ferrocyanide and 3.362 g (i.e., the concentration of Ca(ClO4)2 in the electrolyte is 0.1 mol / L) of Ca(ClO4)2, and stirring for 24 hours to obtain a transparent solution, which is the electrolyte of Example 3 (named B24-0618-BY).

[0094] Example 4

[0095] This embodiment is basically the same as Embodiment 3, except that:

[0096] 0.0303 g (i.e., the concentration of sodium ferrocyanide in the electrolyte is 1 mmol / L) of sodium ferrocyanide was replaced by 1 mmol / L of ascorbic acid; other conditions remained unchanged.

[0097] Example 5

[0098] This embodiment is basically the same as Embodiment 3, except that:

[0099] 0.0303 g (i.e., the concentration of sodium ferrocyanide in the electrolyte is 1 mmol / L) of sodium ferrocyanide was replaced by 1 mmol / L of sodium oxalate; other conditions remained unchanged.

[0100] Example 6

[0101] This embodiment is basically the same as Embodiment 3, except that:

[0102] 0.0303 g (i.e., the concentration of sodium ferrocyanide in the electrolyte is 1 mmol / L) of sodium ferrocyanide was replaced by 1 mmol / L of dodecylamine; other conditions remained unchanged.

[0103] Example 7

[0104] This embodiment is basically the same as Embodiment 3, except that:

[0105] 0.0303 g (i.e., the concentration of sodium ferrocyanide in the electrolyte is 1 mmol / L) of sodium ferrocyanide was replaced by 1 mmol / L of potassium ferrocyanate; other conditions remained unchanged.

[0106] Example 8

[0107] This embodiment is basically the same as Embodiment 3, except that:

[0108] Replace 3.362 g (i.e., the concentration of Ca(ClO4)2 in the electrolyte is 0.1 mol / L) of Ca(ClO4)2 with 0.1 mol / L of barium perchlorate; other conditions remain unchanged.

[0109] Example 9

[0110] This embodiment is basically the same as Embodiment 3, except that:

[0111] Replace 3.362 g (i.e., the concentration of Ca(ClO4)2 in the electrolyte is 0.1 mol / L) of Ca(ClO4)2 with 0.1 mol / L silver perchlorate; other conditions remain unchanged.

[0112] Example 10

[0113] This embodiment is basically the same as Embodiment 3, except that:

[0114] In step 3), the concentration of sodium ferrocyanide was adjusted to 4 mmol / L and the concentration of Ca(ClO4)2 was adjusted to 0.01 mol / L; other conditions remained unchanged.

[0115] Embodiment 11

[0116] This embodiment is basically the same as Embodiment 3, except that:

[0117] In step 3), the concentration of sodium ferrocyanide was adjusted to 50 mmol / L and the concentration of Ca(ClO4)2 was adjusted to 0.5 mol / L; other conditions remained unchanged.

[0118] Example 12

[0119] This embodiment is basically the same as Embodiment 1, except that:

[0120] In step 3), the concentration of Ca(ClO4)2 was adjusted to 0.101 mol / L; other conditions remained unchanged.

[0121] Example 13

[0122] This embodiment is basically the same as Embodiment 2, except that:

[0123] In step 3), the concentration of sodium ferrocyanide was adjusted to 0.101 mol / L; other conditions remained unchanged.

[0124] Comparative Example 1

[0125] This comparative example provides a method for preparing an electrolyte, comprising:

[0126] 1) Mixing fluoroethylene carbonate (FEC), ethylene carbonate (EC) and dimethyl carbonate (DMC) to obtain an electrolyte base solvent; wherein the volume ratio of ethylene carbonate (EC) to dimethyl carbonate (DMC) is 1:1, and the total volume of ethylene carbonate (EC) and dimethyl carbonate (DMC) is 100 mL, and the volume percentage of fluoroethylene carbonate (FEC) in the above electrolyte base solvent is 5%;

[0127] 2) Then, 12.44 g NaClO4 (ie, the concentration of NaClO4 in the electrolyte is 1 mol / L) was added to the electrolyte base solvent and stirred until completely dissolved to obtain the electrolyte of Comparative Example 1 (named B24-0618-KB).

[0128] Test Example 1

[0129] The following parameters of the electrolytes of the above embodiments and comparative examples were tested:

[0130] Water content: Karl Fischer water content test method;

[0131] Hydrohalic acid content: gas chromatography analysis method;

[0132] Conductivity, viscosity: PH balance test method;

[0133] Salting-out temperature: Use a freezer to test the salting-out temperature of the electrolyte at different temperatures;

[0134] Electrolyte application window: linear sweep voltammetry (LSV);

[0135] Characteristic peak of film-forming potential: cyclic voltammetry test (CV).

[0136] Test results

[0137] Table 1

[0138]

[0139] Note: ~2.5 means the average value is 2.5. The same can be applied to other data.

[0140] It can be seen that the hydrohalic acid content of the electrolyte of each embodiment is lower than that of comparative example 1, reflecting that the electrode solution of each embodiment is more stable and has fewer side reactions. In addition, the hydrohalic acid content of Example 3 is lower than that of Examples 12 and 13, reflecting that the cation capture agent and the large-particle metal ions of the embodiments of the present invention have a synergistic effect, which is more conducive to improving the stability of the electrolyte and reducing side reactions.

[0141] Test Example 2

[0142] The electrolytes of the above-mentioned embodiments and comparative examples are used for preparing batteries, including:

[0143] 1) Preparation of manganese iron Prussian blue positive electrode material

[0144] Pump 15L of a mixed solution of manganese sulfate solution and sodium ferrocyanide solution (wherein the concentrations of manganese sulfate and sodium ferrocyanide are 1 mol / L and 0.5 mol / L, respectively) into 10L of a base solution containing sodium sulfate and sodium ferrocyanide (while stirring at a constant temperature of 25°C) to obtain manganese-ferro Prussian white; wherein, in the base solution containing sodium sulfate and sodium ferrocyanide, the concentration of sodium sulfate is 0.1 mol / L, and the concentration of sodium ferrocyanide is 0.002 mol / L;

[0145] Then the temperature was raised and aged at a lower speed of 300 rpm for 8 h;

[0146] Then, after the temperature is lowered to 25°C, 2.5L of a mixed solution of manganese sulfate and ferric sulfate (wherein the concentrations of manganese sulfate and ferric sulfate are 0.9mol / L and 0.45mol / L, respectively) and 4L of a sodium ferrocyanide solution (wherein the concentration of sodium ferrocyanide is 0.413mol / L) are pumped into the above solution again. After the reaction is completed, the temperature is kept constant at 25°C and aged at a lower speed for 6 hours to obtain a manganese iron Prussian blue positive electrode material with a D50 of 5 microns (nitrogen protection is always maintained during the synthesis).

[0147] 2) The above-mentioned manganese iron Prussian blue positive electrode material was dried at 120°C, ball-milled and mixed evenly with SP and PTFE in a mass ratio of 94:2.5:3.5, and then rolled into a film with a thickness of 200 μm, and then rolled with aluminum foil at 170°C to form a Prussian white positive electrode sheet; after drying at above 100°C for 24 hours, the battery was assembled with a hard carbon negative electrode (hard carbon: KB: PVDF = 92:5:3 slurry coated on Al foil), a PP separator, and the electrolyte of each embodiment and comparative example.

[0148] The following parameters were tested on the batteries assembled with the electrolytes of the above embodiments and comparative examples:

[0149] 1) Capacity retention rate after 200 cycles: In a battery test cabinet, charge and discharge cycles are performed at 1C for 200 cycles, and the capacity retention rate is calculated;

[0150] 2) After disassembling the battery after 200 cycles, test the following parameters respectively:

[0151] Cross-sectional scanning of the broken positive electrode active material after 200 cycles: In the drying room, the battery cell after 200 cycles was disassembled, the positive electrode material on the positive electrode sheet was scraped off, and a cross-sectional scanning was performed. Figure 2~Figure 5 ;

[0152] The morphology and porosity of the broken positive electrode active material after 200 cycles: The morphology and porosity were obtained by scanning electron microscopy (SEM) and Best et al. (BET) testing.

[0153] The degree of crushing of the positive electrode active material after 200 cycles: The grains and cross-sections of the positive electrode material were photographed using a scanning electron microscope, and the proportion of crushed particles in the positive electrode material particles (the degree of grain crushing) was observed and calculated;

[0154] The width and length of the cracks on the surface of the grains of the positive electrode active material broken after 200 cycles: the positive electrode material scraped off was ground using an ion milling device to obtain positive electrode material grains with a particle size of 5 μm, and then photographed using a scanning electron microscope to measure the width and length of the cracks on the surface of the positive electrode material grains with a particle size of 5 μm;

[0155] Moisture content of the positive electrode after 200 cycles: discharge in a dry room and disassemble the laminated soft-pack battery after 200 cycles, take out the corresponding positive electrode, vacuum seal it and send it for sample testing;

[0156] The content of iron, manganese and nickel in the electrolyte after 200 cycles: The content of iron, manganese and nickel in the electrolyte was tested using inductively coupled plasma (metal ICP).

[0157] Test results

[0158] Table 2

[0159]

[0160] Table 3 Moisture content in the positive electrode and the content of metal elements in the electrolyte after 200 cycles (unit: ppm)

[0161]

[0162] Note: The manganese content in Examples 1-3 may be 0 or a low level below the detection limit, resulting in it not being detected.

[0163] Combination Figure 1 It can be seen that the electrolyte of Comparative Example 1 does not add any additives, and Example 1 only adds barium perchlorate protective agent; Example 2 only adds cation capture agent sodium ferrocyanide; Example 3 adds both sodium ferrocyanide and barium perchlorate electrolyte additives; after adding the additives, the capacity retention rate of the positive electrode material after 200 cycles is greatly improved, among which Example 3 has the most obvious improvement;

[0164] Combination Figure 2 , Figure 3 , Figure 4 , Figure 5It can be seen that the Ca(ClO4)2 used in Example 1 contains Ca(ClO4)2 with a large ionic radius. 2+ It can enter the Prussian white lattice and occupy sites, inhibiting the sodium hydrate ion (Na(OH2) + ) enters, which is beneficial to the circulation process Na + The repeated deintercalation of water prevents water from re-entering the lattice to occupy active sites, which helps to improve the cycle performance. After 200 cycles, the porosity of the positive electrode material is 16.53%; the sodium ferrocyanide used in Example 2 can effectively capture the Mn dissolved in the charge and discharge process of Prussian white 2+ , Fe 2+ , and then a new Prussian white structure is formed on the surface of the positive electrode Prussian white, which inhibits the structural collapse of the positive electrode active material caused by ion dissolution. After 200 cycles, the porosity of the positive electrode material is 13.89%; Example 3 Since Ca(ClO4)2 and sodium ferrocyanide are used at the same time, the two produce a synergistic effect. On the one hand, they inhibit water from entering the structure again, and on the other hand, they capture the lost metal ions and form a Prussian white structure on the surface again to prevent structural collapse. Together, they help stabilize the Prussian white structure and improve the cycle stability. From the cross-section of the corresponding positive electrode active material, it can be seen that it still maintains intact positive electrode Prussian white cubic particles and high capacity retention rate. After 200 cycles, the porosity of the positive electrode material is only 10.55%.

[0165] The morphology of each component of the battery and the disassembled battery and the porosity of the positive electrode active material after cycling are tested. Specifically, an ion grinder and a SEM electron microscope can be used to observe the crushing of the positive electrode profile, the porosity and the SEM. It can be seen that the electrolyte of Comparative Example 1 is yellowish after cycling, the electrode sheet falls off a lot, and the overall cycle attenuation rate is fast. After 200 cycles, the porosity of the positive electrode material is 29.56%, which indicates that the electrolyte with only EC / DMC and FEC is more prone to metal dissolution and water-electrolyte side reactions.

[0166] from Figure 6 It can be seen that a1 is a physical picture of the battery of comparative example 1 without adding any additives after being disassembled, and it can be seen that its positive electrode active material has obvious metal loss (for example, the yellow-brown color of the electrolyte indicates that Fe ions are dissolved), water escape and electrolyte side reactions and other problems; b1 is a physical picture of the battery of Example 1 with the addition of calcium perchlorate after being disassembled, and c1 is a physical picture of the laminated battery of Example 2 with the addition of sodium ferrocyanide modified electrolyte after being disassembled. It can be seen that the metal loss of the positive electrode active material of these two examples is effectively improved, and the positive electrode sheet almost does not fall off except in the disassembly process, and the surface is smooth and complete, the diaphragm is clean and tidy, and the electrolyte is clear; d1 is a physical picture of the battery of Example 3 with the addition of sodium ferrocyanide and calcium perchlorate electrolyte at the same time after being disassembled, and it can be seen that its material loss, metal loss and electrolyte side reactions are more significantly improved.

[0167] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit it. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present application.

Claims

1. An electrolyte, characterized in that: The electrolyte is used for a battery containing Prussian blue and its analogs, and the electrolyte includes one or more of a cation capture agent and metal ions with an ion radius greater than or equal to 80 nm, wherein the cation capture agent includes a chelating agent.

2. The electrolyte according to claim 1, characterized in that The cation capture agent includes one or more of ferrocyanate, amines, ascorbic acid, and oxalate; the ferrocyanate includes one or more of sodium ferrocyanate and potassium ferrocyanate, and the oxalate includes sodium oxalate; the amine includes one or more of coconut amine, dodecylamine, and octadecylamine; And / or, in the electrolyte, the concentration of the cation capture agent is 1-50 mmol / L.

3. The electrolyte according to claim 1 or 2, characterized in that In the electrolyte, the concentration of the metal ions having an ion radius greater than or equal to 80 nm is 0.01 to 0.5 mol / L; And / or, the metal ions having an ion radius greater than or equal to 80 nm include one or more of calcium, barium, cesium, and silver.

4. The electrolyte according to claim 1 or 2, characterized in that The chemical formula of Prussian blue and its analogs is Na x Mn y Fe z Ni α [Fe(CN)6] β nH2O, where 1.0≤x≤1.5, 0.4≤y≤0.6, 0.4≤z≤0.6, 0.01≤α≤0.03, y+z+α=1, 0.6≤β≤0.8, 0.5≤n≤3.

5. The electrolyte according to claim 1 or 2, characterized in that: The electrolyte also includes electrolyte salt, organic solvent, and film-forming additive. The electrolyte salt includes one or more of sodium perchlorate, sodium hexafluorophosphate, sodium tetrafluoroborate, and organic sodium salts; the organic solvent includes one or more of ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, and vinyl sulfate; the film-forming additive includes one or more of fluoroethylene carbonate, ethylene carbonate, vinyl carbonate, and polystyrene.

6. The electrolyte according to claim 5, characterized in that In the electrolyte, the concentration of the electrolyte salt is 0.3-1.5 mol / L; And / or, the ratio of the volume of the organic solvent to the volume of the electrolyte is 75% to 95%; And / or, the ratio of the volume of the film-forming additive to the volume of the electrolyte is 0-5%.

7. The electrolyte according to claim 1 or 2, characterized in that: The water content of the electrolyte is less than 50 ppm, and the hydrohalic acid content is less than 30 ppm; and / or, at 20-25°C, the conductivity of the electrolyte is 10 -3 ~10 -8 mS / cm, viscosity 5~50mPa·s; And / or, the salting-out temperature of the electrolyte is -25 to 0°C, the application window of the electrolyte is 1.5 to 4.5V, and in a battery containing Prussian blue and its analogs, the characteristic peak of the film-forming potential of the electrolyte is 2.1 to 3.2V.

8. A method for preparing the electrolyte according to any one of claims 1 to 7, characterized in that: include: The cation capture agent and / or the metal salt including the metal ion with an ion radius greater than or equal to 80 nm are dissolved in a raw material system including an organic solvent to obtain the electrolyte.

9. The preparation method according to claim 8, characterized in that: Also includes: Mixing a film-forming additive and an organic solvent to obtain the raw material system including the organic solvent; The electrolyte salt is dissolved in the raw material system including the organic solvent, and then the cation capture agent and the metal salt including the metal ion with an ion radius greater than or equal to 80 nm are dissolved therein to obtain the electrolyte solution.

10. A battery, characterized in that: The invention comprises a positive electrode sheet containing Prussian blue and its analogs and an electrolyte according to any one of claims 1 to 7.

Citation Information

Patent Citations

  • Additive and electrolyte for Prussian blue sodium-ion battery

    CN114243114A

  • Application of sodium ion battery functional additive and sodium ion battery

    CN116525937A

  • Method for improving cyclicity of Prussian blue sodium-ion battery

    CN117913373A

  • Inorganic additives to capture transition metal ions in sodium ion batteries

    CN117981116A

  • Electrolyte additive, electrolyte and battery

    CN118888849A